Design for Motivation to Facilitate the Adoption of Assisted Self-Production in Emerging Economies (Rural and Semi-Urban Context) - Majumdar, Prarthana (My University, 2024)
This research explores the evolution and potential revival of ""Making"" practices in emerging economies, with a focus on India. Historically, Making was essential for survival, but the Industrial Revolution alienated societies from these practices. India's colonial past, where it was deindustrialized to serve British markets, delayed the decline of Making practices compared to the West. Following economic liberalization in the 1990s, cheaper imports led to a reduction in local making activities, contributing to environmental and social issues, including mass migration to urban areas and loss of traditional skills.
Banerjee, Sharmistha